Ultrasound Evaluation of Thyroid Nodules with its Cytological Correlation-An Analytical Cross Sectional Study - Shah, Bhanu Pratap; Singh, Sushma; Khadka, Roshana; Singh, Mrinalani (Annapurna Journal of Health Sciences, 2025)
Introduction: Thyroid nodules, found in 3-7% of the global population, are mostly benign, with 4-6.5% potentially malignant. In Nepal, a hospital based study reported 16.3% malignant and 50% benign cases. Ultrasound (US) is the first-line imaging tool for assessing thyroid nodules, while fine-needle aspiration cytology (FNAC) provides a definitive diagnosis. The objective of this study was to correlate US features with cytological findings in thyroid nodule evaluation. Methods: A prospective analytical cross-sectional study was conducted at Birat Medical College from 5th March to 28th May 2024. Data from 89 patients with thyroid nodules were collected, including baseline history, ultrasound, and FNAC results. Analysis was performed using IBM SPSS v23, with statistical significance set at p < 0.05. Results: The participants had an average age of 49.45 years (±16.033)with a female predominance, though gender did not influence benign or malignant diagnoses(p = 1.000). Statistically significant associations were found between cytological diagnosis and ultrasound features, including larger nodules (>4 cm) (p = 0.038), solitary nodules (40%) (p = 0.000), microcalcifications (p = 0.003), irregular margins (40%) (p = 0.015), and abnormal lymph nodes (p = 0.015). Ultrasound's sensitivity, specificity, PPV, and NPV were 60%, 96.4%, 50%, and 97.6%, respectively. Conclusion: The study demonstrates that ultrasound features such as nodule size, composition, microcalcifications, irregular margins, and lymph node abnormalities significantly correlate with cytological findings. Ultrasound, when combined with cytology, enhances diagnostic accuracy in distinguishing between benign and malignant thyroid nodules.